2022
DOI: 10.3389/fonc.2022.857515
|View full text |Cite
|
Sign up to set email alerts
|

Management of BRCA Tumour Testing in an Integrated Molecular Tumour Board Multidisciplinary Model

Abstract: Tumour testing of the BRCA1/2 genes is routinely performed in patients with different cancer histological subtypes. To accurately identify patients with tumour-detected germline pathogenic variants (PVs) is a relevant issue currently under investigation. This study aims at evaluating the performance of the tumour-to-germline diagnostic flowchart model defined at our Institutional Molecular Tumour Board (MTB). Results from tumour BRCA sequencing of 641 consecutive unselected cancer patients were discussed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Since NGS BRCA1/2 tumour testing was not available before 2017 in our Institution, 19 of 222 subjects underwent germline testing before tumour sequencing based on personal (very early age at diagnosis/previous breast cancer) or family history. According to the workflow used by our Molecular Tumour Board (MTB), in 73 out of 203 patients with upfront tumour testing subsequently received genetic counselling, either for targeted germline sequencing of a tumour-detected PV or for large genomic rearrangement analysis 14 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since NGS BRCA1/2 tumour testing was not available before 2017 in our Institution, 19 of 222 subjects underwent germline testing before tumour sequencing based on personal (very early age at diagnosis/previous breast cancer) or family history. According to the workflow used by our Molecular Tumour Board (MTB), in 73 out of 203 patients with upfront tumour testing subsequently received genetic counselling, either for targeted germline sequencing of a tumour-detected PV or for large genomic rearrangement analysis 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, this multidisciplinary approach proved effective also when applied to tumours for which clinical, molecular, pathology and immunohistochemistry data have to be integrated, as in the case of colorectal cancer 13 . In our previous study, we showed that the tumour-to-germline approach could detect and overcome potential technical limitations of tumour sample analysis in identifying putative germline variants 14 , which may lead to low sensitivity for large genomic rearrangements detection, misinterpretation of secondary “reverse” mutations or reduced sequencing accuracy at loci with homopolymeric repeats.…”
Section: Introductionmentioning
confidence: 99%